The psychosocial impact of the Romanian government measures on the population during the COVID-19 pandemic - Androniceanu, Armenia (Central European Public Administration Review, 2021)
The Covid-19 pandemic generated a global crisis involving most countries in the world. State governments worldwide were forced to take appropriate measures impacting different fields. The Romanian government and other local public authorities developed special measures to curb the spread of the SARS-COV-2 virus in Romania in general and in Bucharest, the country's capital. The purpose of our research was to identify the social and psychological impact of the governmental measures on the citizens of Bucharest. The research was conducted between 28 November and 25 December 2020, but refers to the measures taken by the government and local authorities from the onset of the Covid-19 pandemic to date. The sample, representative for Bucharest, included 421 citizens living in Bucharest, aged between 19 and 40 years. The data were collected using an online questionnaire. Other methods used to analyse the results and verify the hypothesis included the multiple regression model and some applications in Excel. The results confirmed that governmental measures had a strong social and psychological impact on citizens, changing their social behaviour and causing psychological disorders, such as depression and anxiety. Our research results can help the Romanian authorities avoid problems among the population and adapt their measures to better meet the population's psychosocial needs in time of the Covid-19 pandemic crisis, which is far from over.
Keywords: Covid-19; družbeni vpliv; governmental policy; pandemic; pandemija; psihološki vpliv; psychological impact; social impact; vladna politika